Lean into Clinical Pharmacy: An Experience in Implementing Key Performance Indicators and Gemba Walks into Clinical Pharmacy Services - Jocelyn Owusu-Guha (University of Minnesota Libraries Publishing, 2021)
Purpose: The Lean methodology was applied to clinical metrics by a critical care pharmacy team. The experiences associated with the development and implementation of clinical metrics and their impact on daily workflow are described.